PENGARUH MEDIA VISUAL MENGGUNAKAN PROYEKTOR DIGITAL TERHADAP HASIL BELAJAR APRESIASI SENI RUPA SISWA KELAS VII SMP NEGERI 25 PADANG - FERA INDIKAWATI, Dr.Ramalis Hakim, M.Pd. Drs. Ajusril S (Serupa The Journal of Art Education, 2015)
This study aims to look at the influence of learning outcomes appreciation of art students, both high initial knowledgeable students and students who are knowledgeable lower initial visual media that taught using a digital projector. This research is a quantitative experiment, the population in this study were students of class VII SMP 25 Padang, the sampling technique is in Random / Random Simple (Simple Random Sampling), which VII.3 grade students as an experimental class while the class VII.5 as class control the number of 28 students in each class. Based on the results of data processing obtained an average student learning outcomes experimental class was 76.6, the average result was 63.9 class learning control. In the experimental class average of student learning outcomes of knowledge is 83.1 and the high initial class of students who are knowledgeable initial control high is 70.6. In the experimental class average of student learning outcomes are knowledgeable lower initial 76.3 and the control class students who are knowledgeable initial low is 67.5. Based on the results anlisis be seen that the use of visual media using a digital projector to improve learning outcomes appreciation of art students.Kata kunci: Pengaruh, media, hasil belajar